The Use of Landsat 8 in Detecting Potential Mineral Zones in West Nusa Tenggara, Indonesia - Said Umar Abdulrahim; Bantan Rashad A.; Mannaa Ammar A.; Taufiq Yasser (Russian Journal of Earth Sciences, 2024)
The remote sensing analysis within the Hu'u District area is known to face a challenge with dense vegetation. The problem affects the accurate reading of spectral reflectance from satellites, influencing the differentiation between potential mineral zones and vegetation. Therefore, this study aims to carry out a remote sensing analysis of densely vegetated areas to differentiate minerals from vegetation and obtain potential mineral zones. The combination band ratios and principal component analysis (PCA) methods are used to acquire potential mineral zones. Furthermore, Landsat 8 images freely available on Google Earth Engine are adopted and the validation is carried out using a drill hole from previous study. The results show that band ratios method cannot distinguish mineral zones from vegetation. However, PCA method can recognize potential mineral zones. This is the result from PCA method with band combination of bands 1, 2, 3, 4, 5, and 6 as the first group and band 2, 4, 5, and 6 as the second group.